Ethical Pluralism in AI Policy: A Framework for Islamic Integration into Global AI Governance - Muchtasor, Nisrina Salwa (Sinergi International Journal of Islamic Studies, 2025)
The rapid adoption of artificial intelligence (AI) has intensified global efforts to establish ethical and legal governance. While frameworks such as the EU AI Act, NIST AI Risk Management Framework (RMF), UNESCO Recommendation on AI Ethics, and OECD AI Principles provide foundational guidelines, they often lack culturally grounded ethical perspectives. This study proposes integrating Maqāṣid al-Sharīʿah—the higher objectives of Islamic law—as a complementary ethical layer within global AI governance. Using a comparative conceptual mapping approach, the research analyzes the alignment between Maqāṣid principles and global standards through policy reviews, AI ethics literature, and Islamic jurisprudence. Findings reveal strong thematic compatibility between Maqāṣid domains (protection of religion, life, intellect, lineage, and property) and principles emphasized by UNESCO and the OECD, including shared opposition to biometric surveillance and social scoring. A governance model is introduced by overlaying Maqāṣid criteria onto the NIST RMF structure (GOVERN, MAP, MEASURE, MANAGE), offering a culturally coherent implementation strategy. Integrating Maqāṣid al-Sharīʿah enhances normative legitimacy in Muslim-majority contexts and promotes a pluralistic, ethically resilient AI policy landscape, demonstrating that religious ethics can enrich international standards for responsible AI.